2019
DOI: 10.1039/c9cc01587f
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of an improved transglucosylase for production of the rare sugar nigerose

Abstract: Sucrose phosphorylase was redesigned to vastly improve its ability to produce a promising rare sugar from abundant bulk sugars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…All chemicals were of analytical grade and were obtained from Sigma-Aldrich/Merck (Darmstadt, Germany) or Carbosynth (Berkshire, United Kingdom), except for psicose (Izumori Lab, Kagawa University, Kagawa, Japan), glycerol (Chem-Lab, Zedelgem, Belgium), tagatose (Nutrilab, Giessen, The Netherlands) and trehalose (Cargill, Vilvoorde, Belgium). Kojibiose, nigerose and βGlc1P were produced in-house according to the procedures of Beerens et al [ 51 ], Franceus et al [ 52 ] and Van der Borght et al [ 53 ], respectively.…”
Section: Methodsmentioning
confidence: 99%
“…All chemicals were of analytical grade and were obtained from Sigma-Aldrich/Merck (Darmstadt, Germany) or Carbosynth (Berkshire, United Kingdom), except for psicose (Izumori Lab, Kagawa University, Kagawa, Japan), glycerol (Chem-Lab, Zedelgem, Belgium), tagatose (Nutrilab, Giessen, The Netherlands) and trehalose (Cargill, Vilvoorde, Belgium). Kojibiose, nigerose and βGlc1P were produced in-house according to the procedures of Beerens et al [ 51 ], Franceus et al [ 52 ] and Van der Borght et al [ 53 ], respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In a different study, the Q345F variant was further engineered in order to improve the activity and selectivity of SP towards nigerose formation without the need for a cosolvent. A quadruple mutant (R135Y-D342G-Y344Q-Q345F) was designed that forms nigerose with greater selectivity and a 68-fold improved catalytic efficiency in aqueous solution [77]. Molecular dynamics simulations suggested that the acceptor site of the quadruple mutant is more flexible than the one of the Q345F mutant, offering a possible explanation for its enhanced properties.…”
Section: Engineering Of Specificity or Selectivitymentioning
confidence: 99%
“…‘Rare sugars’, which are defined by the International Society of Rare Sugars as ‘monosaccharides and their derivatives that are present in limited quantities in nature’, may be promising sugar replacers, based on studies reporting low caloric content and reduced glycemic responses for rare sugars, such as allulose and tagatose, compared to conventional sugars [ 8 , 9 ]. Recently, rare sugars also attracted attention due to innovative biocatalysis strategies that allow efficient production of these otherwise insufficiently available sugars, including biosynthesis of the rare glucobioses kojibiose [ 10 ] and nigerose [ 11 ] (visualized in Figure 1 ) from widely available sugars using (engineered) sucrase phosphorylase [ 12 , 13 ]. These innovations allow further research on the metabolic health impact of rare sugars, which is still in an early stage, especially for rare disaccharides [ 14 ].…”
Section: Introductionmentioning
confidence: 99%